A study to assess effectiveness of video assisted teaching programme on gastro intestinal tract assessment among student nurses of tertiary care hospital: a statistical approach - Bhosale, Trupti S.; Bhosale, Sagar B.; Zagade, Tukaram B.; Kakade, Satish V. (International Journal of Research in Medical Sciences, 2019)
Background: The gastro intestinal is important system in the human body. Many times it is found that its uneasy for student nurses to check the patient. So, there is need to improve the available learning programmes regarding gastro intestinal tract assessment.So, it was necessary to conduct this study for educating student nurses regarding the gastro intestinal tract assessment to improve their knowledge. The objectives of this study were to assess the knowledge of student nurses regarding gastro-intestinal tract assessment and to evaluate the effectiveness of video assisted teaching programme on knowledge regarding gastro intestinal tract assessment. Methods: Material and methods used for the study is the evaluative approach; one group pre test, post test design was used. Study was conducted on sample of 70 student nurses by using convenient sampling technique. The data were collected by structured questionnaire. The data were analyzed using descriptive and inferential statistics. Results: The mean knowledge score of student nurses during the pre-test was 39.89% where as it had raised up to 72% during the post-test regarding gastro intestinal tract assessment as effectiveness of video assisted teaching programme. Therefore, the difference assessed was 32.11% between pre-test and post-test. Conclusions: There was significant difference between the pre-test knowledge level and post-test knowledge level of student nurses on gastro intestinal tract assessment. Hence health education programs and on-going teaching both can further improve the knowledge of student nurses.